Fresh and Mechanical Properties of Self-Compacting Rubber Lightweight Aggregate Concrete and Corresponding Mortar - Jing Lv; Qiang Du; Tianhua Zhou; Zuoqian He; Kunlun Li (Advances in Materials Science and Engineering)
Increasing amount of waste tires caused huge environment issues in recent years. Recycling concrete is an effective way. In this paper, waste tires are crushed into particles and incorporated in lightweight aggregate concrete to prepare a special concrete (self-compacting rubber lightweight aggregate concrete (SCRLC)). A detailed experimental research of effects of rubber particles on the properties of SCRLC and corresponding mortar is conducted. The results show that increasing the rubber particles replacement ratio leads to a raising of yield stress and plastic viscosity of mortar pastes. Flowability, filling capacity, and passing ability of SCRLC decline and the segregation resistance property of SCRLC improves as the rubber particles replacement ratio increases. Well, linear correlations between slump flow of SCRLC and shear stress of corresponding mortar pastes and segregation ratio of SCRLC and plastic viscosity of corresponding mortar pastes are obtained. In order to ensure that rubber lightweight aggregate concrete can compact by itself, the upper limit of shear stress of corresponding mortar pastes is 231.7 Pa and the lower limit of plastic viscosity of corresponding mortar pastes is 3.72 Pa·s. Compressive strength, splitting tensile strength, flexural strength, and elastic modulus of SCRLC and compressive strength of corresponding mortar decrease as the rubber particles replacement ratio increases. The 28-day compressive strength of SCRLC can meet the requirements of lightweight aggregate concrete structures until the rubber particles replacement ratio reaches 50%.